PENGARUH MOTIVASI, KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA PERANGKAT KELURAHAN DI KECAMATAN KARANGANYAR KABUPATEN KARANGANYAR - Erica Murwidyawan, Dian Esti Nurati & Maya Sekarwangi (JI@P, 2019)
The study purposes were examined (1) the effect of competence,motivation, and work environment on performance of urban villageofficers in Karanganyar Sub District of Karanganyar Regency; (2) theeffect of motivation on the performance urban village officers inKaranganyar Sub District of Karanganyar Regency; (3) the effect ofcompetence on performance of urban village officers in Karanganyar SubDistrict of Karanganyar Regency; and (4) the effect of work environmenton performance of urban village officers in Karanganyar Sub District ofKaranganyar Regency. This study was used descriptive research withquantitative approach. This research objects are urban village officer inKaranganyar Sub-district, Karanganyar Regency. The samplingtechnique was used random sampling. The study data were used primaryand secondary data. Data collection techniques were used questionnaires,observations, and documentation. Hypothesis testing was used t test andF test. The study results were shown that: (1) Work motivation,competence, and work environment simultaneously influences to theperformance of urban village officers in Karanganyar Sub District ofKaranganyar Regency; (2) Motivation is influences to the performance ofurban village officers in Karanganyar Sub District of KaranganyarRegency; (3) Competence is influence to the performance of urbanvillage officers in Karanganyar Sub District of Karanganyar Regency;and (4) Working environment is influence to the performance of urbanvillage officers in Karanganyar Sub District of Karanganyar Regency.Keywords: motivation, competence, work environment, performance